483 SHAPE MEMORY POLYMER NEUROVASCULAR STENTS. (1st January 2006) - Baer, G.; Wilson, T.; Maitland, D.; Matthews, D.
Abstract : Stroke is the third leading cause of death in the United States and the major cause of long-term disability. Ischemic strokes represent the majority of cases. The only approved treatment available to restore blood flow in small intracranial vessels consists of drug therapy (rtPA). However, it is associated with a limited window of opportunity and risks of hemorrhage. Stents are now widely used in order to restore blood flow in larger arteries, but considering the current technology of stents, no such devices are available for intracranial arteries due to the tortuosity of the neurovasculature, the small diameter, and the delicacy of the vessels. We hypothesized that stents made of shape memory polymer (SMP) could be engineered to be placed in intracranial vessels. Due to its phase separation occurring during polymerization, the polymer we are proposing to use has a unique ability to be deformed and to recover a predetermined shape. The material can be molded into a primary shape, corresponding here to the final shape of the stent implanted in the artery; it can then be deformed into a secondary shape, here a small collapsed device to be inserted into the artery; finally, it can recover its primary shape upon heat activation. The polymeric material can also be coated for biocompatibility and drug release. In this study, we describe preliminary work towards the development of a shape memory polymer stent to be placed in the neurovasculature. We first describe the thermomechanical properties of SMP polyurethane. Second, we evaluate the forces exerted on the device during actuation and after implantation; these forces are then measured experimentally. Finally, we propose to test the prototype for deliverability and deployability in ex vivo arteries.